A shift to shorter cuticular hydrocarbons accompanies sexual isolation among Drosophila americana group populations. Issue 5 (1st October 2021) - Davis, Jeremy S.; Pearcy, Matthew J.; Yew, Joanne Y.; Moyle, Leonie C.
Abstract: Because sensory signals often evolve rapidly, they could be instrumental in the emergence of reproductive isolation between species. However, pinpointing their specific contribution to isolating barriers, and the mechanisms underlying their divergence, remains challenging. Here, we demonstrate sexual isolation due to divergence in chemical signals between two populations of Drosophila americana (SC and NE) and one population of D. novamexicana, and dissect its underlying phenotypic and genetic mechanisms. Mating trials revealed strong sexual isolation between Drosophila novamexicana males and SC Drosophila americana females, as well as more moderate bi-directional isolation between D. americana populations. Mating behavior data indicate SC D. americana males have the highest courtship efficiency and, unlike males of the other populations, are accepted by females of all species. Quantification of cuticular hydrocarbon (CHC) profiles—chemosensory signals that are used for species recognition and mate finding in Drosophila —shows that the SC D. americana population differs from the other populations primarily on the basis of compound carbon chain-length. Moreover, manipulation of male CHC composition via heterospecific perfuming—specifically perfuming D. novamexicana males with SC D. americana males—abolishes their sexual isolation from these D. americana females. Of a set of candidates, a single gene—elongase CG17821—had patterns of gene expression consistent with a role in CHC differences between species. Sequence comparisons indicate D. novamexicana and our Nebraska (NE) D. americana population share a derived CG17821 truncation mutation that could also contribute to their shared "short" CHC phenotype. Together, these data suggest an evolutionary model for the origin and spread of this allele and its consequences for CHC divergence and sexual isolation in this group.